Effect of irrigation practices on stream depletion in the Arikaree River, eastern Colorado - Griffin, Steven D., author; Oad, Ramchand Naraindas, advisor; Bledsoe, Brian P., committee member; Smith, Freeman M. (Freeman Minson), 1939-, committee member (Colorado State University. Libraries, 2004)
Irrigated agriculture is of paramount importance to the economy and livelihoods of those living in much of Eastern Colorado. Here, wells feeding center pivot systems draw groundwater from the High Plains Aquifer, and are commonly employed to supplement the meager amounts of natural precipitation. It is commonly accepted that a well actively pumping in the vicinity of a natural stream or river could, under certain circumstances, divert water from the stream itself and/or divert baseflow away from the river. Recent studies conducted on the Arikaree River, located in Yuma County, Colorado, have shown a clear pattern of stream drying during the growing season. The river, fully connected and flowing during the winter months, eventually becomes a series of standing pools and dry runs until the return of flow late in the calendar year. The river is almost entirely fed by groundwater via springs and seeps along its reach. In order to preserve the riparian ecosystem in the Arikaree River valley (including a threatened species of fish, Hybognathus hankinsoni also known as the Brassy Minnow), the true nature of the stream depletion must first be found. Irrigation practices of several farmers in the vicinity of the Arikaree were determined for 2003, while stage height in the river was monitored. It was found that initial declines in stage height were nearly temporally identical for 2002 and 2003 . It was also found that most irrigation began 2-4 weeks later in 2003 than it had in 2002. Thus, the change in irrigation practices did not appear to impact stream depletion rates between these two years. Most stage height declines appeared in the record several weeks before the onset of the bulk of high-capacity pumping in the area, suggesting that there may be other factors besides irrigated agriculture contributing to the seasonal stream depletion. Results of a simplified stream-depletion model currently used for water rights administration are presented, as well as data regarding the permeability of the Arikaree streambed at various locations along its reach. Recommendations are also made concerning future research and data collection to further determine the effect of irrigation on the Arikaree River.
Keywords: Irrigation -- Environmental aspects -- Colorado -- Yuma County; Groundwater flow -- Colorado -- Yuma County